BS EN ISO 16784-1 Corrosion of metals and alloys. Corrosion and fouling in industrial cooling water systems. Guidelines for conducting pilot-scale evaluation of corrosion and fouling control additives for open recirculating cooling water systems (12th September 2023) - British Standards Institution,
No abstract available